Spread of clonal genovar E Chlamydia trachomatis among men who have sex with men - Arabella Touati (Public Library of Science (PLoS), 2021)
In a previous study, we developed a Multi-Locus VNTRs Analysis (MLVA) typing system, called MLVA-5, for the discrimination of Chlamydia trachomatis genovar E strain. The results suggested the clonal spread of a MLVA-5 type 21 strain among men who have sex with men (MSM). We applied the MLVA-5 typing method on 157 French anorectal genovar E specimens and 19 Swedish specimens collected between 2010 and 2015. A total of 29 MLVA-5 types was obtained, with three predominant types among French samples: 78 specimens belonged to MLVA-5 type 21, two other types, 11 and 13, included 9 and 14 specimens, respectively. In 15 cases, one unique MLVA-5 type was observed for a single patient, 7 of which were new types not previously described. The distribution of MLVA-5 types according to sexual orientation showed that the 7 anorectal specimens from heterosexual patients belonged to 6 genotypes, and the 12 anorectal specimens from bisexual patients comprised eight types. The 95 anorectal specimens from MSM were distributed into 22 types, but 55 (57.9%) of them belonged to MLVA-5 type 21. Among the Swedish specimens from MSM, eight were from MLVA-type 21 (4 urines and 4 anorectal specimens). The results support the hypothesis of the spread of clonal genovar E strain among MSM.